Review of various scoring systems for screening of chronic sensorimotor peripheral neuropathy in Type II Diabetes Mellitus - Agrawal, Pooja; Goel, Amrit; Gupta, Supriya (Journal of Neonatal Surgery, 2025)
Diabetic peripheral neuropathy (DPN) is one of the most common microvascular complications in type 2 diabetes mellitus. Nerve conduction study (NCS) has long been a minimal criterion or a gold standard test for confirming the diagnosis of peripheral neuropathies. Potential disadvantages of NCS are limited availability for routine diagnostic evaluation of DPN and insensitive for the identification of small‐fibre neuropathy. Many diagnostic tests have been designed to screen and diagnose peripheral neuropathy in individuals with diabetes, but there exists a disagreement as to which is the most appropriate and reliable clinical neuropathy scale for peripheral neuropathy in patients with diabetes.This narrative review aims to summarise the existing knowledge of different scoring systems with respect to NCS for screening of chronic sensorimotor diabetic peripheral neuropathy in type 2 diabetics.